Lama Screen Time Menggunakan Gadget Terhadap Perkembangan Sosial Pada Anak Prasekolah - Brivian Florentis Yustanta; Varin Sonna Fitrian (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Preschool age children inevitably have to live side by side with technological advances. With the limited learning system during the Covid-19 Pandemic, they had to do screen time using gadgets to access learning media. The purpose of this study was to determine the correlation between the length of screen time using gadgets on the social development of preschool children. The research design used correlational analytic with cross sectional approach. The independent variable in this study was the length of screen time using gadgets, while the dependent variable was the social development of preschool children. The study was conducted at Al Ibrah Gresik Integrated Islamic Kindergarten and Dharma Wanita Persatuan Kindergarten, Gresik Sub District, Gresik Regency on April 4-9, 2022. The population in this study were mothers of 72 preschoolers. The sampling technique used proportional random sampling, so that a sample size of 65 was obtained. Instruments The research instrument was modified of Dortmund Developmental Screening Preschool (DDSP) questionnaire. Statistical test analysis using Spearman Sign Rank Test. The test results obtained p value of 0.002 < 0.05 and a correlation coefficient of 0.650, meaning that there was a strong correlation between the length of screen time using gadgets and social development in preschoolers. The higher the duration of screen time, it can cause social development disorders.